Pregnancy complications and premature cardiovascular events among 1.6 million California pregnancies. Issue 1 (25th February 2019) - Arnaout, Rima; Nah, Gregory; Marcus, Greg; Tseng, Zian; Foster, Elyse; Harris, Ian S; Divanji, Punag; Klein, Liviu; Gonzalez, Juan; Parikh, Nisha
Abstract : Background: Cardiovascular complications of pregnancy present an opportunity to assess risk for subsequent cardiovascular disease. We sought to determine whether peripartum cardiomyopathy and hypertensive disorder of pregnancy subtypes predict future myocardial infarction, heart failure or stroke independent of one another and of other risks such as gestational diabetes, preterm birth and intrauterine growth restriction. Methods and results: The California Healthcare Cost and Utilization Project database was used to identify all hospitalised pregnancies from 2005 to 2009, with follow-up through 2011, for a retrospective cohort study. Pregnancies, exposures, covariates and outcomes were defined by International Classification of Diseases, Ninth Revision codes. Among 1.6 million pregnancies (mean age 28 years; median follow-up time to event excluding censoring 2.7 years), 558 cases of peripartum cardiomyopathy, 123 603 hypertensive disorders of pregnancy, 107 636 cases of gestational diabetes, 116 768 preterm births and 23 504 cases of intrauterine growth restriction were observed. Using multivariable Cox proportional hazards models, peripartum cardiomyopathy was independently associated with a 39.2-fold increase in heart failure (95% CI 30.0 to 51.9), resulting in ~1 additional hospitalisation per 1000 person-years. There was a 13.0-fold increase in myocardial infarction (95% CI 4.1 to 40.9) and a 7.7-fold increase in stroke (95% CI 2.4 to 24.0). Hypertensive disorders of pregnancy were associated with 1.4-fold (95% CI 1.0 to 2.0) to 7.6-fold (95% CI 5.4 to 10.7) higher risk of myocardial infarction, heart failure and stroke, resulting in a maximum of ~1 additional event per 1000 person-years. Gestational diabetes, preterm birth and intrauterine growth restriction had more modest associations. Conclusion: These findings support close monitoring of women with cardiovascular pregnancy complications for prevention of early cardiovascular events and study of mechanisms underlying their development.